2016
DOI: 10.1155/2016/8491046
|View full text |Cite
|
Sign up to set email alerts
|

A System for True and False Memory Prediction Based on 2D and 3D Educational Contents and EEG Brain Signals

Abstract: We studied the impact of 2D and 3D educational contents on learning and memory recall using electroencephalography (EEG) brain signals. For this purpose, we adopted a classification approach that predicts true and false memories in case of both short term memory (STM) and long term memory (LTM) and helps to decide whether there is a difference between the impact of 2D and 3D educational contents. In this approach, EEG brain signals are converted into topomaps and then discriminative features are extracted from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Finally, the discriminative features were input to the simple and efficient CMMDC to predict whether a subject belongs to HA or LA group in raw as well as clean data, classify the correct and incorrect answers, and classify EO and EC brain states. The detail of the experimental material, subjects, data collection procedure and processing EEG signals after recording is discussed in [33,34].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, the discriminative features were input to the simple and efficient CMMDC to predict whether a subject belongs to HA or LA group in raw as well as clean data, classify the correct and incorrect answers, and classify EO and EC brain states. The detail of the experimental material, subjects, data collection procedure and processing EEG signals after recording is discussed in [33,34].…”
Section: Methodsmentioning
confidence: 99%
“…In eyes open / eyes closed (EOEC) dataset, thirty subjects (34) subjects were participated in the baseline task, i.e. EO and EC.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CNN and LSTM neural network's results were much better than the MLP's results, achieving an accuracy of 94.16% compared to the MLP's 82.50% accuracy, which, as the authors say, "clearly demonstrated that temporal information is important for signal analysis". Bamatraf et al (2016) chose SVM with RBF kernel to classify (predict) true and false memories, both short term memories (STM) and long term memories (LTM). The data was collected by an EEG device while the learners watched learning material; half the learners watched in 2D, and the other half watched the same material in 3D.…”
Section: Overview Of the Studiesmentioning
confidence: 99%
“…As such the pivotal question, as to whether brain activity during the initial memory encoding and consolidation or long-term retrieval differs in relation to whether items are subsequently remembered or missed, is a possibility to be explored [4] . Neuroimaging, in particular functional magnetic resonance imaging (fMRI) [5] and neurophysiological measures such as intracranial electroencephalogram (iEEG) [6] , has allowed researchers to extend behavioral research and establish a relationship between generalized patterns of brain activity and cognitive processes that support memory formation and retrieval [7] [9] .…”
Section: Introductionmentioning
confidence: 99%